Operative Outcome of Ruptured Saccular Aneurysm of the Anterior Cerebral Circulation at Siriraj Hospital : A Personal Series - Prajak Saesue (Siriraj Medical Journal, 2002)
This retrospective study analysed the data regarding the operative outcome of patients who had subarachnoid hemorrhage (SAH) from rupture of a saccular aneurysm of the anterior cerebral circulation. All patients were operated on by the author between July 1997 and November 2001 at Siriraj Hospital. A total of 62 patients were included in this study. All patients were assessed on admission using Hunt and Hess classification. There were 5 patients (8.1%) in Grade 1, 12 patients (19.4%) in Grade 2, 37 patients (59.7%) in Grade 3, 7 patients (11.3%) in Grade 4, and 1 patient (1.6%) in Grade 5. A uniform management protocol was used in every patient including intensive cardiovascular monitoring, calcium channel blocker administration, early surgery clipping the aneurysm and aggressive anti-ischemic treatment. There were 22 patients (35.5%) who received early surgery (within 72 hours of the SAH), 12 patients (19.4%) received intermediate surgery (between Day 4 and day 6 following SAH) and 28 individuals (45.1%) had late surgery (Day 7 or later following SAH). At 6 months after the SAH, favorable outcome (Glasgow Outcome Scale: GOS 1 and 2) was achieved in 55 patients (88.7%), unfavorable outcome (GOS 3 and 4) in 1 patient (1.6%) and death in 6 patients (9.7%). The causes of death were surgically related in 3 patients (4.8%) and non-surgically related (delayed ischemic complication and sepsis) in 3 patients (4.8%).